Ways of Looking: The Composite Novel and Posthuman Community in Jon McGregor's Reservoir 13 - Adele Guyton (C21 Literature: Journal of 21st-century Writings, 2023)
Jon McGregor’s Reservoir 13 (2017) is set in an unnamed village in the UK’s Peak District and, in thirteen chapters that each cover a year, depicts the everyday lives of the humans, plants and animals in that area. The novel is notable for giving equal emotional significance to human and non-human life, and for being composed of vignettes focused on characters or groups that are arranged chronologically without deference to a dramatic arc. These characteristics ally Reservoir 13 with the contemporary novels being categorised as narratives of community or composite novels, which often use locations to bring together disparate characters. Within this context, Reservoir 13’s unusual highlighting of non-human life raises questions about how the place of the non-human in literary community is framed by composite or fragmented narrative structures. This paper concludes that Reservoir 13 can be seen as an example of a posthuman literary community: through its fragmented structure, externally focalised narration, and inclusion of disparate forms of human and non-human life, McGregor crafts a community not as it might be experienced by one human – the bird’s eye view of the third-person narrator covers too much ground for this – but as a theoretical perspective. In the nascent field of posthuman narratology, Reservoir 13 is a uniquely apt case study for showing how twenty-first century writing might construct a posthuman community with the conundrum of the anthropocentrism and humanism of the novel form lurking in the background.